Fostering nursing through management : a critical approach : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Nursing Studies at Massey University - Russell, Lyneta (Massey University, 1993)
This study reveals for critique the philosophical and ideological forces which currently shape the perceptions of a small group of nurse managers in one acute care hospital setting. It has as its aim action to overcome constraints and to realize opportunities in the nurse manager position. Nurse managers assume central ward management and clinical responsibilities. This study describes how they can adjust to changes in these responsibilities within a changing health care structure and at the same time maintain and foster a nursing focus within their work. Using the research methods of critical social science this research explores central themes in the work and world of nurse managers. Through critical dialogue and reflection nurse managers are given opportunities to explore the social, political and historical forces that shape their understanding of their position, and to critique those forces. This critical process assists nurse managers to move towards a new understanding of their position and empowers them towards emancipatory action.
Keywords: Training of Nurse administrators; Nursing services; Administration